Corticospinal excitability in idiopathic normal pressure hydrocephalus: a transcranial magnetic stimulation study - Jani Sirkka; Laura Säisänen; Petro Julkunen; Mervi Könönen; Elisa Kallioniemi; Ville Leinonen; Nils Danner (Fluids and Barriers of the CNS, 2020)
Abstract Background Idiopathic normal pressure hydrocephalus (iNPH) is a neurodegenerative disease with an unknown etiology. Disturbed corticospinal inhibition of the motor cortex has been reported in iNPH and can be evaluated in a noninvasive and painless manner using navigated transcranial magnetic stimulation (nTMS). This is the first study to characterize the immediate impact of cerebrospinal fluid (CSF) drainage on corticospinal excitability. Methods Twenty patients with possible or probable iNPH (16 women and 4 men, mean age 74.4 years, range 67–84 years), presenting the classical symptom triad and radiological findings, were evaluated with motor function tests (10-m walk test, Grooved Pegboard and Box & Block test) and nTMS (silent period, SP, resting motor threshold, RMT and input–output curve, IO-curve). Evaluations were performed at baseline and repeated immediately after CSF drainage via lumbar puncture. Results At baseline, iNPH patients presented shorter SPs (p < 0.001) and lower RMTs (p < 0.001) as compared to normative values. Positive correlation was detected between SP duration and Box & Block test (rho = 0.64, p = 0.002) in iNPH patients. CSF drainage led to an enhancement in gait velocity (p = 0.002) and a steeper IO-curve slope (p = 0.049). Conclusions Shorter SPs and lower RMTs in iNPH suggest impaired corticospinal inhibition and corticospinal hyperexcitability. The steeper IO-slope in patients who improve their gait velocity after CSF drainage may indicate a higher recovery potential. Corticospinal excitability correlated with the motor function of the upper limbs implying that the disturbance in motor performance in iNPH extends beyond the classically reported gait impairment.